Ответ:
1) a² + 16a - 4 + a = a² + 17a - 4
2) x² + 4y² - 2y + 9a² + 4y² + 3a - 2y = x² + 8y² + 3a
3) (8a - 4) - (a - yb) + (x² + 25y² - 5y) = 8a - a + yb + x² + 25y² - 5y - 4 = 8a + yb + x² + 25y² - 5y - 4
4) (3a - 2y)(xy) + (2y - x)(a - by) = 3a xy - 2xy² + 2ay - 3ab + bx
5) (2a - by)(by - 2a) / (10ху - 5y + х) = - (2a - by)(2a - by) / (5(2ху - у + 2х)) = - (2a - by)² / (10ху - 5y + 2х - у)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
1) a² + 16a - 4 + a = a² + 17a - 4
2) x² + 4y² - 2y + 9a² + 4y² + 3a - 2y = x² + 8y² + 3a
3) (8a - 4) - (a - yb) + (x² + 25y² - 5y) = 8a - a + yb + x² + 25y² - 5y - 4 = 8a + yb + x² + 25y² - 5y - 4
4) (3a - 2y)(xy) + (2y - x)(a - by) = 3a xy - 2xy² + 2ay - 3ab + bx
5) (2a - by)(by - 2a) / (10ху - 5y + х) = - (2a - by)(2a - by) / (5(2ху - у + 2х)) = - (2a - by)² / (10ху - 5y + 2х - у)